Human Mediation between Mother Animals and Their Young in Livestock Reproduction – a Case Study on Lamb Bags - Haiyan Bao; Jiligen Fu; Takahiro Ozaki; Zhenzhen Liu; Saqiri (Nomadic Peoples, 2024)
In pastoral society, the reproduction of livestock is directly related to the survival and prosperity of herders. The key to domestic animal reproduction lies in the cognitive bond between mother livestock and their young. Herdsmen use various tools and techniques to help develop this cognitive bond. These human mediation tools have various characteristics such as ‘restorative’ or ‘destructive’. The lamb bag, a widely used tool in pastoral society, has both ‘restorative’ and ‘destructive’ natures. Based on ethnographic data collected in Inner Mongolia, China, this paper first introduces the production method of lamb bags, then describes their structure, function and the multi-dimensional relationships generated during the application process, and finally discusses the cultural implications of ‘restorative’ and ‘destructive’ human mediation in pastoral culture.